1989
DOI: 10.1002/j.1460-2075.1989.tb08396.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible abrogation of IL-3 dependence by an inducible H-ras oncogene.

Abstract: Immortalized, interleukin-3 (I-3)-dependent mouse mast cells (PB-3c) were transfected with a human activated c-H-ras gene under the transcriptional control of the mouse mammary tumor virus long terminal repeat. Addition of increasing amounts of dexamethasone resulted in a concentration-dependent increase in expression of the H-ras oncogene. The elevation of p21 ras protein concentrations was paralleled by progressive growth of the transfectants in the absence of exogenous IL-3, leading to complete abrogation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Inhibition of ras expression has been reported to precede, and perhaps be a prerequisite for apoptosis of cultured chloroleukemic cells (Servomaa & Rytomaa, 1988). In a mouse mast cell line transfected with human activated Ha-ras oncogene in a regulable construct, ras activation was also associated with rapid growth, whilst reduced ras expression was accompanied by cell death (Andrejauskas & Moroni, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of ras expression has been reported to precede, and perhaps be a prerequisite for apoptosis of cultured chloroleukemic cells (Servomaa & Rytomaa, 1988). In a mouse mast cell line transfected with human activated Ha-ras oncogene in a regulable construct, ras activation was also associated with rapid growth, whilst reduced ras expression was accompanied by cell death (Andrejauskas & Moroni, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Work in our laboratory has shown that PB-3c cells can progress to IL-3-producing autocrine mastocytomas after introduction of the v-Ha-ras oncogene (15). In addition, production of IL-3 and GM-CSF can be induced in PB-3c cells transfected with the vector expressing the EJ c-Ha-ras oncogene at high levels (36). Overexpression of a transforming ras p21 protein, which shares structural homology with guanine nucleotide-binding proteins (37) …”
Section: Discussionmentioning
confidence: 99%
“…IL-3 binding leads to b-chain autophosphorylation on tyrosine residues and activation of the Jak-Stat, mitogen-activated protein kinases (MAPK) and PI3K-/PKB pathways resulting in proliferation and inhibition of apoptosis (for references see Blalock et al (1999)). IL-3-independent growth has been observed via activating mutations of the common IL-3R b-subunit (D'Andrea et al, 1994;Hannemann et al, 1995;McCormack and Gonda, 1997) and a variety of mechanisms involving bcr-abl (Jiang et al, 2002), v-erbB (Shounan et al, 1995;McCubrey et al, 2004), v-src (Overell et al, 1987), c-kit (Piao and Bernstein, 1996), activated Stat5 (Onishi et al, 1998) pim-1 (Nosaka and Kitamura, 2002), Flt3 (Hayakawa et al, 2000), mpl (Onishi et al, 1996b) and H-ras (Andrejauskas and Moroni, 1989). For a recent review see Steelman et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…IL-3-independent growth, however, occurred following conditional expression of the human H-Ras gene at very high levels from a MMTV-long terminal repeat (LTR), which allowed cells to switch from IL-3-dependent to inducer (dexamethasone)-dependent growth and back (Andrejauskas and Moroni, 1989). Weaker expression of v-H-ras, driven by a Moloney LTR, led to a reduction in the requirement of exogenous IL-3, but not to autonomous growth.…”
Section: Introductionmentioning
confidence: 99%